The war of the worlds - Vogel, Malvina G.; Lynch, Brendan; Wells, H. G. (Herbert George), 1866-1946. (New York : Waldman & Son, 1983)
Humans battle evil aliens to save Earth and its people from certain doom when the Martians land in England.
Keywords: Adventure and adventures -- Fiction; War -- Fiction; Science fiction